High-reflection glaze layer with composite structure, manufacturing method of high-reflection glaze layer, backboard glass and photovoltaic module

By applying a composite structure of a high-reflection glaze layer on the backplane glass, combined with the design of high-temperature bonding phase and white filler stacking layer, the problems of low reflectivity and poor glaze layer structure in the prior art are solved, and high-efficiency light is achieved Both recycling and glass loading.

CN119118527AActive Publication Date: 2024-12-13SHANGHAI NEXOLAR NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411168929.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The reflective glaze layer of existing backplane glass has a low reflectivity and low light energy utilization rate, which leads to limited power generation efficiency of photovoltaic modules. At the same time, the glaze layer structure is poor, affecting the glass strength and load capacity.

Method used

Using a highly reflective glaze layer with a composite structure, including a surface layer and a reflective layer. The surface layer is a high-temperature bonded phase stacking layer and a white filler stacking layer. The light recycling rate is improved through mixed reflection (diffuse and directional reflection), and Protect the reflective layer structure during tempering.

Benefits of technology

It significantly improves the recycling rate of light, enhances the water vapor insulation and electrical insulation properties of the glaze layer, reduces the impact of the glaze layer on the glass load, and ensures the strength and durability of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118527A_ABST
    Figure CN119118527A_ABST
Patent Text Reader

Abstract

The invention provides a high-reflection glaze layer with a composite structure and a manufacturing method thereof, back plate glass and a photovoltaic module, the high-reflection glaze layer with the composite structure is arranged on base material glass and comprises a surface layer and a reflection layer, the surface layer is arranged on the surface layer, and the reflection layer is arranged on the back plate glass. The surface layer covers the surface and the side surface of the reflecting layer, and the tail end of the surface layer is in contact with the surface of the base material glass; the surface layer is a high-temperature binding phase accumulation layer, and the reflecting layer is a white filler accumulation layer. The high-reflection glaze layer with the composite structure provided by the invention is compact in surface, has an obvious layered structure, can form multi-gradient reflection, and has excellent reflection capability, so that interstitial light can be more sufficiently recycled; and meanwhile, the water vapor insulation and electrical insulation properties of the glaze layer are greatly improved, and both the PCT 96-hour test and the PID 192-hour test pass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-reflection glaze layer with a composite structure and a manufacturing method thereof, back plate glass and a photovoltaic module, belonging to the technical field of photovoltaic modules. Background Art

[0002] In order to recycle light, the glaze layer on the surface of the commercially available backplane grid glass mostly uses a white reflective glaze layer, which is formed by printing glass ink on the glass surface once and then tempering. This glaze layer has disadvantages such as low reflectivity / light energy utilization, affecting glass load / reducing glass strength. Specifically, the reflectivity of this glaze layer is concentrated at around 75%, and the utilization rate of light is not high, and it is all diffusely reflected light, that is, the glaze layer recycles light in the form of diffuse reflection, and the proportion of reflected light actually returning to the surface of the battery cell is not high, so the component gain brought is also limited. At the same time, the glass often accommodates the sintering temperature of the glaze layer during the tempering process, so the tempering strength of the glass itself will be affected, and the glaze performance cannot match the glass performance well, resulting in serious expansion of microcracks on the glass surface, which in turn seriously reduces the strength of the backplane glass; in other words, because the glaze layer structure has the disadvantages of non-denseness and expansion mismatch, the glaze layer tempering process window is narrow, the aging resistance is weak, and the glass strength is seriously affected.

[0003] The utilization rate of light determines the power generation efficiency of photovoltaic solar panels. At present, most photovoltaic solar panels inevitably have certain gaps between cells and strings, and the area of ​​such gaps accounts for 7%-15% of the entire panel. How to efficiently recycle and utilize this part of the projected light is particularly important.

[0004] As the weight of photovoltaic modules continues to decrease, the backplane glass will inevitably become larger and thinner. The performance of most white glaze layers on 2.0mm glass backplanes on the market can no longer meet the load requirements of module manufacturers. As the glass continues to become thinner, the load impact of such glaze layers on the glass will also increase.

[0005] Therefore, providing a new type of high-reflection glaze layer with a composite structure and a manufacturing method thereof, back panel glass and photovoltaic module has become a technical problem that urgently needs to be solved in the field. Summary of the invention

[0006] In order to solve the above shortcomings and deficiencies, the purpose of the present invention is to provide a high-reflection glaze layer with a composite structure and a method for making the same, a backplane glass and a photovoltaic module. The high-reflection glaze layer provided by the present invention has a composite layer structure, so that it can achieve multi-gradient and multi-dimensional mixed reflection (diffuse reflection and directional reflection). After being arranged on the surface of the substrate glass, the resulting backplane glass can more reasonably and fully recycle the interstitial light, has a very high light recycling rate, and can also maximize the glass load without being affected.

[0007] In order to achieve the above objectives, on the one hand, the present invention provides a high-reflection glaze layer with a composite structure, which is arranged on a substrate glass, wherein the high-reflection glaze layer with a composite structure comprises a surface layer and a reflective layer, the surface layer covers the surface and side surfaces of the reflective layer and the end of the surface layer contacts the surface of the substrate glass;

[0008] Wherein, the surface layer is a high-temperature bonding phase accumulation layer, and the reflective layer is a white filler accumulation layer.

[0009] As a specific embodiment of the above-mentioned high reflective glaze layer of the present invention, the surface layer further comprises a white filler, and the white filler is evenly distributed in the high-temperature bonding phase accumulation layer. The white filler in the surface layer is either mixed into the surface layer from the reflective layer when preparing the high reflective glaze layer, or is added to the surface layer when preparing the high reflective glaze layer.

[0010] In the above-mentioned high-reflection glaze layer of the present invention, the surface layer contains a high-temperature bonding phase and a white filler, wherein the high-temperature bonding phase is piled up to form a high-whiteness layer structure, and the white filler is distributed / filled between the layer structures. The surface layer is a dense structure, which can protect the reflective layer structure from water vapor erosion to the greatest extent, and at the same time provide the best water vapor insulation properties, thereby playing a role in protecting the reflective layer; in addition to diffuse reflection on the surface of the surface layer, the dense and smooth dense glaze layer can also provide partial directional reflection light under a specific angle of incidence, so that the high-reflection glaze layer can improve the recycling rate of light through mixed reflection (diffuse reflection plus directional reflection).

[0011] As a specific embodiment of the above-mentioned high reflective glaze layer of the present invention, wherein the white filler includes titanium dioxide, etc., and based on the total weight of the surface layer as 100%, the content of TiO2 in the surface layer is ≤50%, preferably 25-45%.

[0012] As a specific embodiment of the above-mentioned high-reflective glaze layer of the present invention, the whiteness L value of the surface layer is ≥98.5.

[0013] As a specific embodiment of the above-mentioned high-reflection glaze layer of the present invention, D97 of the high-temperature bonding phase in the surface layer is ≤8 μm.

[0014] As a specific embodiment of the above-mentioned high reflective glaze layer of the present invention, the white filler in the reflective layer includes at least one of titanium dioxide, barium sulfate, silicon microspheres, porcelain powder, etc., and the content of the white filler in the reflective layer is ≥40%, preferably 40-60%, based on the total weight of the reflective layer as 100%. When the white filler in the reflective layer is titanium dioxide, the content of the white filler in the reflective layer can be calculated as the content of TiO2.

[0015] As a specific implementation of the above-mentioned high-reflective glaze layer of the present invention, wherein the whiteness L value of the reflective layer is ≥98.5.

[0016] As a specific embodiment of the above-mentioned high-reflection glaze layer of the present invention, the D97 of the white filler in the reflective layer is less than 10 μm.

[0017] In the above-mentioned high-reflection glaze layer of the present invention, the reflective layer is mainly used to provide basic reflectivity, and is mainly diffuse reflection, which can more efficiently scatter and reflect the light that is not recovered on the surface layer and then recycle it. Such a structural design allows the reflection and recovery of light to be more sufficient and more gradient. In addition to diffuse reflection, there is also a certain amount of directional reflection of light; compared with the surface layer, the material accumulation in the reflective layer is obviously loose.

[0018] As a specific embodiment of the high reflective glaze layer described above in the present invention, the thickness of the surface layer accounts for 1 / 4-1 / 2 of the total thickness of the high reflective glaze layer, and the thickness of the reflective layer accounts for 1 / 2-3 / 4 of the total thickness of the high reflective glaze layer.

[0019] As a specific embodiment of the above-mentioned high-reflection glaze layer of the present invention, the thickness of the surface layer is 5-20 μm, and the thickness of the reflective layer is 8-25 μm.

[0020] As a specific embodiment of the above-mentioned high-reflection glaze layer of the present invention, the thickness of the high-reflection glaze layer with a composite structure is 18-30 μm.

[0021] As a specific embodiment of the above-mentioned high-reflection glaze layer of the present invention, there are clear boundaries between the reflective layer and the surface layer, and between the reflective layer and the surface of the substrate glass.

[0022] On the other hand, the present invention also provides a method for manufacturing the above-mentioned high-reflective glaze layer with a composite structure, wherein the manufacturing method comprises:

[0023] Step (1): uniformly mixing the high-temperature binder phase and the first varnish to obtain a first slurry;

[0024] Step (2): uniformly mixing the white filler and the second varnish to obtain a second slurry;

[0025] Step (3): coating the second slurry and the first slurry on the substrate glass in sequence, and then tempering the substrate glass in a furnace to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0026] The first varnish and the second varnish used in step (1) and step (2) of the above-described production method of the present invention are both conventional substances and can be reasonably selected according to needs; and the first varnish and the second varnish can be the same or different, and are preferably the same.

[0027] As a specific implementation of the above-mentioned manufacturing method of the present invention, the coating includes printing, roller coating or spraying, etc. In some embodiments of the present invention, the printing includes screen printing, overprinting and other printing methods.

[0028] As a specific implementation of the above-mentioned manufacturing method of the present invention, the temperature of the furnace tempering is 690-740° C. and the time is 90-115 seconds.

[0029] Since the high-reflection glaze layer provided by the present invention has a composite layer structure, the structure is more reasonable, so that the sintering window is wider, and during the furnace tempering process, the tempering characteristics and tempering process of the glass itself will not be affected.

[0030] On the other hand, the present invention further provides a back panel glass, comprising a substrate glass and a glaze layer arranged on the surface thereof, wherein the glaze layer is the high-reflection glaze layer with a composite structure as described above.

[0031] In yet another aspect, the present invention further provides a photovoltaic module, wherein the photovoltaic module comprises the back panel glass described above.

[0032] As a specific implementation of the photovoltaic module described above in the present invention, the photovoltaic module is a double-glass photovoltaic solar module.

[0033] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0034] The high-reflection glaze layer with a composite structure provided by the present invention comprises a reflective layer and a surface layer, wherein the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass; wherein the surface layer contains a high-temperature bonding phase and the reflective layer contains white filler.

[0035] First of all, the high-reflection glaze layer with a composite structure has a clear / obvious layered structure and each layer plays a different role. The surface layer is a dense high-temperature bonding phase accumulation layer, which can improve the light recovery rate by mixed reflection (diffuse reflection plus directional reflection); and the surface layer has a dense structure, which can protect the reflective layer structure from water vapor erosion to the greatest extent and provide the best water vapor insulation properties; and the reflective layer is a high-whiteness white filler accumulation layer, which can further recycle the light. Such a structural design allows the reflection and recovery of light to be more sufficient and more gradient. In addition to diffuse reflection, there is also a certain amount of directional reflection light. That is, the present invention reasonably designs the layer structure of the high-reflection glaze layer so that the glaze layer has multi-gradient, multi-dimensional mixed reflection (diffuse reflection and directional reflection), so that the interstitial light can be recycled more reasonably and fully.

[0036] Secondly, in addition to more sufficient light energy recovery, the composite structure design in the high-reflective glaze layer greatly reduces the existence of independent pores and through pores in the entire glaze layer, making the glaze layer structure denser, more stable and reliable, and avoiding the intrusion of water vapor during later storage and testing. The water vapor insulation and electrical insulation properties of the glaze layer are also better improved and the performance is maintained longer, making the weather resistance test of the components under long-term use more reliable.

[0037] Thirdly, in the contact area between the high-reflection glaze layer and the substrate glass, the vast majority of the contact area is mainly in non-erosive contact with the reflective layer, and a very small part of the contact area is in continuous and dense contact with the surface layer. This structural design reduces the area of ​​the continuous and dense contact points between the glaze layer and the substrate glass, thereby minimizing the impact of the erosion of the substrate glass by the glaze layer and the difference in the physical properties of the two materials on the substrate glass load, providing a more reliable and safer glaze solution for the enlargement and thinning of photovoltaic glass. After the high-reflection glaze layer with a composite structure provided by the present invention is set on the surface of the substrate glass, the load of the substrate glass is almost unaffected, and the drop ball impact height is close to that of the bare glass.

[0038] In addition, in addition to more sufficient recycling of light energy, the back glass with a high-reflection glaze layer with a composite structure on the surface has an extremely high light recovery rate. The reflection curve in the full band (380-1200nm) is raised as a whole, and the maximum reflection range (480-980nm) is also more in line with the spectral response band of photovoltaic cells. That is, the highest reflectivity point moves back to 480-980nm, which is more in line with the best response band of the battery cell.

[0039] In summary, the high-reflection glaze layer with a composite structure provided by the present invention has a dense surface and a distinct layered structure, which can form multi-gradient reflection and has excellent reflection ability, so that the interstitial light can be more fully recycled; at the same time, the water vapor insulation and electrical insulation performance of the glaze layer have also been greatly improved, and the PCT96-hour test and PID192-hour test have both passed. In addition, the load of the backplane glass provided with the high-reflection glaze layer with a composite structure is almost unaffected, and the height of the ball dropped at any position of the blank screen printing surface is the same as that of the bare chip, and the impact height of the ball dropped at the cross intersection of the non-screen printing surface is close to that of the bare chip glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 This is a simplified schematic diagram of the structure of the back panel glass provided in Example 1 of the present invention.

[0042] Figure 2a This is a local scanning electron microscope image of the middle position of the back panel glass provided in Example 1 of the present invention.

[0043] Figure 2b This is a local scanning electron microscope image of the middle position of the back panel glass provided for Comparative Example 1.

[0044] Figure 3 This is a simplified schematic diagram of the structure of the back panel glass provided for Comparative Example 1.

[0045] Figure 4 This is the reflectivity curve of the back panel glass provided in Example 1 obtained in Test Example 2 of the present invention.

[0046] Description of main figures:

[0047] 1. Surface layer;

[0048] 2. Reflective layer;

[0049] 3. Base material glass;

[0050] 4. White glaze layer. DETAILED DESCRIPTION

[0051] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0052] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0053] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0054] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0055] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0056] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0058] The "thickness" in the present invention means the "average thickness".

[0059] Example 1

[0060] This embodiment provides a back plate glass, and its structure schematic diagram is as follows Figure 1 As shown, from Figure 1 It can be seen that it includes a substrate glass 3 and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass 3. The high-reflection glaze layer with a composite structure includes a reflective layer 2 and a surface layer 1. The surface layer 1 covers the surface and side of the reflective layer 2 and the end of the surface layer 1 is in contact with the surface of the substrate glass 3. There are clear boundaries between the surface layer 1 and the reflective layer 2, and between the reflective layer 2 and the substrate glass 3.

[0061] The surface layer 1 is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer 1 is 8 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0062] The reflective layer 2 is a white filler accumulation layer. Compared with the surface layer 1, the accumulation of the reflective layer 2 material is obviously loose, mainly used to provide basic reflectivity, and mainly diffuse reflection. Its thickness is 16μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0063] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0064] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0065] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0066] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0067] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0068] Example 2

[0069] This embodiment provides a back panel glass, which is different from the embodiment 1 only in that the substrate glass is embossed ultra-white glass.

[0070] Example 3

[0071] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0072] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 12 μm, accounting for 1 / 2 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0073] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 12μm, accounting for 1 / 2 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0074] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0075] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0076] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0077] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0078] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0079] Example 4

[0080] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0081] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 6 μm, accounting for 1 / 4 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0082] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 18μm, accounting for 3 / 4 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0083] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0084] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0085] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0086] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0087] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0088] Example 5

[0089] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0090] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 10 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0091] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 20μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0092] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0093] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0094] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0095] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0096] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0097] Example 6

[0098] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0099] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 6 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0100] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 12μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0101] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0102] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0103] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0104] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0105] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0106] Example 7

[0107] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0108] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 13.3 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0109] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose, mainly used to provide basic reflectivity, and mainly diffuse reflection. Its thickness is 26.7μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0110] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0111] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0112] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0113] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0114] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0115] Example 8

[0116] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0117] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 4 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0118] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 8μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0119] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0120] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0121] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0122] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0123] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0124] Example 9

[0125] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0126] The surface layer is a high-temperature bonding phase (i.e., glass powder) accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 8 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 45%;

[0127] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 16μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 30%;

[0128] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0129] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0130] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0131] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0132] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0133] Example 10

[0134] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0135] The surface layer is a high-temperature bonding phase accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 8 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 55%;

[0136] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 16μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0137] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0138] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0139] Step (1): uniformly mixing titanium dioxide, glass powder and a first varnish (commercially available conventional varnish) to obtain a first slurry;

[0140] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0141] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0142] Embodiment 11

[0143] This embodiment provides a back plate glass, which includes a substrate glass and a high-reflection glaze layer with a composite structure arranged on the surface of the substrate glass, the high-reflection glaze layer with a composite structure includes a reflective layer and a surface layer, the surface layer covers the surface and side of the reflective layer and the end of the surface layer contacts the surface of the substrate glass, and there are clear boundaries between the surface layer and the reflective layer, and between the reflective layer and the substrate glass;

[0144] The surface layer is a high-temperature bonding phase accumulation layer, forming a dense high-whiteness reflective layer, which mainly protects the entire multi-layer structure. The thickness of the surface layer is 8 μm, accounting for 1 / 3 of the total thickness of the high-reflective glaze layer. The surface layer contains titanium dioxide, which is evenly distributed in the high-temperature bonding phase accumulation layer. The total weight of the surface layer is 100%, and the content of TiO2 in the surface layer is 65%;

[0145] The reflective layer is a white filler accumulation layer. Compared with the surface layer, the accumulation of the reflective layer material is obviously loose. It is mainly used to provide basic reflectivity and is mainly diffuse reflection. Its thickness is 16μm, accounting for 2 / 3 of the total thickness of the high-reflective glaze layer. The reflective layer contains titanium dioxide and glass powder. The total weight of the reflective layer is 100%, and the content of TiO2 in the reflective layer is 50%;

[0146] The substrate glass is ultra-white float glass, and its thickness is 2.0 mm.

[0147] In order to more fully introduce the back plate glass, this embodiment also provides a manufacturing method thereof, including:

[0148] Step (1): mixing glass powder and a first varnish (commercially available conventional varnish) uniformly to obtain a first slurry;

[0149] Step (2): uniformly mixing titanium dioxide, glass powder and a second varnish (commercially available conventional varnish) to obtain a second slurry;

[0150] Step (3): The second slurry and the first slurry are applied to form a grid on the surface of the substrate glass by silk screen overprinting, and then tempered in a furnace at 690-740° C. for 90-115 seconds to form a high-reflection glaze layer with a composite structure on the substrate glass.

[0151] Example 12

[0152] This embodiment provides a back plate glass, which is different from the embodiment 1 only in that the surface layer of the high reflective glaze layer with a composite structure does not contain titanium dioxide.

[0153] Comparative Example 1

[0154] This comparative example provides a back plate glass, and its structure schematic diagram is as follows Figure 3 As shown, from Figure 3 As can be seen, it includes a substrate glass and a white glaze layer arranged on the surface of the substrate glass. The white glaze layer is formed by printing glass ink on the surface of the substrate glass once, with a printing thickness of 24 μm, and then curing and tempering.

[0155] Wherein, the substrate glass is float ultra-white glass, and its thickness is 2.0 mm.

[0156] Comparative Example 2

[0157] This comparative example provides a back plate glass, and its structure schematic diagram is as follows Figure 3 As shown, from Figure 3 As can be seen, it includes a substrate glass and a white glaze layer arranged on the surface of the substrate glass. The white glaze layer is formed by printing glass ink on the surface of the substrate glass once, with a printing thickness of 24 μm, and then curing and tempering.

[0158] Wherein, the substrate glass is embossed ultra-white glass, and its thickness is 2.0 mm.

[0159] Test Example 1

[0160] In this test example, local electron microscope scanning is performed on the middle position of the back plate glass provided in Example 1 of the present invention and the back plate glass provided in Comparative Example 1. The scanning electron microscope image of the back plate glass of Example 1 is as follows: Figure 2a As shown, the scanning electron microscope image of the back glass of Comparative Example 1 is as follows Figure 2b As shown. Figure 2a and Figure 2bIt can be seen that in the back panel glass provided in Example 1, the high-reflection glaze layer with a composite structure is arranged on the surface of the substrate glass, and there are clear interfaces between the surface layer and the reflective layer in the high-reflection glaze layer with a composite structure, and between the reflective layer and the substrate glass, and the base layer contains titanium dioxide and a glass phase, while the surface layer contains a glass phase and titanium dioxide uniformly distributed in the glass phase.

[0161] Test Example 2

[0162] In this test example, the back glass provided by Examples 1 to 12 of the present invention and the back glass provided by Comparative Examples 1 to 2 are tested for reflectivity, hundred-grid strength, pencil hardness, PCT 96-hour test, PID 192-hour test, glass surface stress test, four-point bending test and impact height test, wherein the reflectivity is tested using a spectrophotometer with a test band of 380-1200nm; the hundred-grid strength is tested using a hundred-grid knife; the pencil hardness is tested using a pencil hardness tester; the PCT 96-hour test is conducted using a high-pressure constant temperature chamber with test conditions of 121°C, 100% humidity, saturated vapor pressure and continuous Run for 96 hours, observe whether the glaze layer changes during the test, and whether the reflectivity attenuation is ≤2%; PID192-hour test is to test the back glass with glaze layer after lamination and sealing it into components. The test conditions are temperature 85°C, relative humidity 85%, DC power on, voltage set to 1500V and continuous operation for 192 hours. Observe whether the glaze layer changes in color during the test; Glass surface stress is tested by surface stress meter; Four-point bending is tested by four-point bending tester and the falling ball impact height is tested using plastic sleeve and 227g steel ball. The test starts from 0.6 meters, with 50mm as an interval, and gradually increases.

[0163] In this test example, the reflectivity test, the hundred-grid strength test, the pencil hardness test, the PCT 96-hour test, and the PID 192-hour test results of the back glass provided by Examples 1 to 12 of the present invention and Comparative Examples 1 and 2 are respectively as shown in Tables 1 and Figure 4 shown.

[0164] Table 1

[0165]

[0166] In this test example, the test results of the drop ball impact height of the back panel glass provided by Examples 1 to 12 of the present invention and Comparative Examples 1 and 2 are shown in Table 2 below.

[0167] Table 2

[0168]

[0169]

[0170] The reflectivity curve of the back plate glass provided in Example 1 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure is as follows: Figure 4 As shown, Figure 4 The reflectivity curve shown is relatively smooth, with an average reflectivity of more than 89.6%. Figure 4 It can be seen that on the float ultra-white glass, the reflectivity curve shows the best reflectivity at 580-780nm, and the average reflectivity in this band is above 89%, which is very consistent with the response range of the battery cell; the overall reflectivity in the 480-980nm band is above 88%. From the experimental data in Table 1 above, it can be seen that the hundred-grid strength of the backplane glass provided in Example 1 is level 0, and the pencil hardness is >6H; after the PCT 96-hour test, the glaze layer has no obvious changes; and under the PID 192-hour test, the glaze layer has no discoloration. From the experimental data in Table 2 above, it can be seen that for the backplane glass provided in Example 1, the falling ball impact height is close to the bare chip, the blank area of ​​the printed surface is 1.8m, the T-shaped part of the non-silk-screen printed surface is 1.6m, and the middle cross part is 1.4m. The load of the glass itself is not greatly affected.

[0171] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 2 of the present invention, that is, the embossed ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface has a reflectivity of 92.3%, a hundred-grid strength of 0, and a pencil hardness of >6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0172] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the screen printing surface is 1.6m, the T-shaped area of ​​the non-screen printing surface is 1.4m, and the cross area in the middle is 1.2m. The load of the glass itself is not greatly affected.

[0173] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 3 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 86.5%, a hundred-grid strength of 0, and a pencil hardness of >6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0174] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.8m, the T-shaped area of ​​the non-screen printed surface is 1.4m, and the cross area in the middle is 1.2m. The load on the glass itself is not greatly affected.

[0175] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 4 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 90.2%, a hundred-grid strength of 0-1, and a pencil hardness>4H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0176] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.8m, the T-shaped area of ​​the non-screen printed surface is 1.4m, and the cross area in the middle is 1.2m. The load on the glass itself is not greatly affected.

[0177] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 5 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 85.8%, a hundred-grid strength of 0, and a pencil hardness>6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0178] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.4m, the T-shaped area on the edge of the non-screen printed surface is 1.2m, and the cross area in the middle is 1.0m.

[0179] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 6 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 88.8%, a hundred-grid strength of 1, and a pencil hardness>6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0180] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.7m, the T-shaped area on the edge of the non-screen printed surface is 1.5m, and the cross area in the middle is 1.3m.

[0181] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 7 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 85.6%, a hundred-grid strength of 0, and a pencil hardness>6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0182] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.2m, the T-shaped area on the edge of the non-screen printed surface is 1.0m, and the cross area in the middle is 0.9m.

[0183] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 8 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 88.4%, a hundred-grid strength of 1, and a pencil hardness>4H; after the PCT 96-hour test, the glaze layer has no obvious change; but under the PID 192-hour test, the glaze layer is partially delaminated;

[0184] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.8m, the T-shaped area on the edge of the non-screen printed surface is 1.5m, and the cross area in the middle is 1.4m.

[0185] Compared with Examples 5 and 6, the thickness of the high-reflective glaze layer with a composite structure in Example 7 of the present invention is too thick. Although the performance of the glaze layer meets the requirements, it does not meet the demand for a thinner glaze layer. The thickness of the high-reflective glaze layer with a composite structure in Example 8 is too thin. Although the performance of the glaze layer barely meets the requirements, its durability is slightly poor.

[0186] From the experimental data in Table 1 and Table 2 above, it can be seen that the back glass provided in Example 9 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 82.4%, a hundred-grid strength of 0, and a pencil hardness>6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0187] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.0m, the T-shaped area on the edge of the non-screen printed surface is 0.9m, and the cross area in the middle is 0.8m.

[0188] Compared with Example 1, in the high-reflective glaze layer with a composite structure provided in Example 9 of the present invention, the content of TiO2 in the reflective layer is too low, only 30%. Although the performance of the glaze layer basically meets the requirements, its reflectivity is relatively low.

[0189] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 10 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 81.4%, a hundred-grid strength of level 2, and a pencil hardness of >3H; it cannot pass the PCT 96-hour test and the PID 192-hour test;

[0190] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.4m, the T-shaped area on the edge of the non-screen printed surface is 1.2m, and the cross area in the middle is 0.9m.

[0191] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 11 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 82.2%, a hundred-grid strength of 4, and a pencil hardness of >2H; it cannot pass the PCT 96-hour test and the PID 192-hour test;

[0192] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.5m, the T-shaped area on the edge of the non-screen printed surface is 1.3m, and the cross area in the middle is 1.0m.

[0193] Compared with Example 1, in the high-reflective glaze layer with a composite structure provided by Examples 10 and 11 of the present invention, the TiO2 content in the surface layer is too high, so that the strength and other properties of the glaze layer are significantly reduced; and by comparing the data of the glaze layers provided by Examples 10 and 11, it can be seen that with the increase of the TiO2 content in the surface layer, the strength and other properties of the glaze layer are further reduced.

[0194] From the experimental data in Table 1 and Table 2 above, it can be seen that the back plate glass provided in Example 12 of the present invention, that is, the float ultra-white glass with a thickness of 2.0 mm and a high-reflection glaze layer with a composite structure on the surface, has a reflectivity of 81.6%, a hundred-grid strength of 0, and a pencil hardness>6H; the glaze layer has no obvious change after the PCT 96-hour test; and the glaze layer has no color change after the PID 192-hour test;

[0195] The impact height of the falling ball is close to that of the bare chip, the blank area of ​​the printed surface is 1.8m, the T-shaped area on the edge of the non-screen printed surface is 1.6m, and the cross area in the middle is 1.4m.

[0196] By comparing the experimental results of the back panel glass provided in Example 1 and Example 12 of the present invention, it can be seen that when the surface layer of the high-reflection glaze layer with a composite structure of the back panel glass does not contain titanium dioxide, the 100-grid strength test, pencil hardness test, PCT 96-hour test and PID 192-hour test results of the back panel glass do not change significantly, but its reflectivity is low, at only 81.6%.

[0197] From the experimental data in Table 1 and Table 2 above, it can be seen that the back glass provided in Comparative Example 1, i.e., the float ultra-white glass with a white glaze layer on the surface, has a reflectivity of 80%, a hundred-grid strength of 0-1, and a pencil hardness>4H; the glaze layer partially fails in the PCT 96-hour test; and the glaze layer partially delaminates in the PID 192-hour test;

[0198] Drop ball impact height: 1.3m for blank area of ​​silk-screen printed surface, 1.0m for T-shaped area on the edge of non-silk-screen printed surface, and 0.9m for the cross area in the middle.

[0199] From the experimental data in Table 1 and Table 2 above, it can be seen that the back glass provided in Comparative Example 2, i.e., the embossed ultra-white glass with a white glaze layer on the surface, has a reflectivity of 82%, a hundred-grid strength of 0-1, and a pencil hardness>4H; after the PCT 96-hour test, the glaze layer has local failure; and after the PID 192-hour test, the glaze layer has local delamination;

[0200] Drop ball impact height: 1.2m for blank area of ​​silk-screen printed surface, 0.9m for T-shaped area on the edge of non-silk-screen printed surface, and 0.8m for the cross area in the middle.

[0201] From the above experimental results, it can be seen that the high-reflection glaze layer with a composite structure provided by the embodiment of the present invention has a dense surface and a distinct layered structure, which can form multi-gradient reflection and has excellent reflection ability, so that the interstitial light can be more fully recycled; at the same time, the water vapor insulation and electrical insulation performance of the glaze layer are also greatly improved. In addition, the load of the backplane glass provided with the high-reflection glaze layer with a composite structure is almost unaffected, and the height of the ball dropped at any position of the blank screen printing surface is the same as that of the bare chip, and the impact height of the ball dropped at the cross intersection of the non-screen printing surface is close to that of the bare chip glass.

[0202] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A highly reflective glaze layer with a composite structure, which is arranged on a substrate glass, It is characterized in that The high-reflection glaze layer with a composite structure comprises a surface layer and a reflective layer, wherein the surface layer covers the surface and side surfaces of the reflective layer and the end of the surface layer contacts the surface of the substrate glass; Wherein, the surface layer is a high-temperature bonding phase accumulation layer, and the reflective layer is a white filler accumulation layer.

2. The high reflective glaze layer according to claim 1, It is characterized in that The surface layer also contains white fillers, which are evenly distributed in the high-temperature bonding phase stacking layer.

3. The high reflective glaze layer according to claim 2, It is characterized in that The white filler includes titanium dioxide, and based on the total weight of the surface layer as 100%, the TiO 2 The content is ≤50%, preferably 25-45%.

4. The high reflective glaze layer according to any one of claims 1 to 3, It is characterized in that The whiteness L value of the surface layer is ≥98.

5.

5. The high reflective glaze layer according to any one of claims 1 to 3, It is characterized in that The D97 of the high temperature bonding phase in the surface layer is ≤8 μm.

6. The high reflective glaze layer according to claim 1, It is characterized in that The white filler in the reflective layer includes at least one of titanium dioxide, barium sulfate, silicon microspheres and ceramic powder. Based on the total weight of the reflective layer as 100%, the content of the white filler in the reflective layer is ≥40%, preferably 40-60%.

7. The high reflective glaze layer according to claim 1 or 6, It is characterized in that The whiteness L value of the reflective layer is ≥98.

5.

8. The high reflective glaze layer according to claim 1 or 6, It is characterized in that The D97 of the white filler in the reflective layer is less than 10 μm.

9. The high reflective glaze layer according to any one of claims 1 to 3 and 6, It is characterized in that The thickness of the surface layer accounts for 1 / 4-1 / 2 of the total thickness of the high-reflection glaze layer, and the thickness of the reflective layer accounts for 1 / 2-3 / 4 of the total thickness of the high-reflection glaze layer.

10. The high reflective glaze layer according to any one of claims 1 to 3 and 6, It is characterized in that The thickness of the surface layer is 5-20 μm, and the thickness of the reflective layer is 8-25 μm.

11. The high reflective glaze layer according to any one of claims 1 to 3 and 6, It is characterized in that The thickness of the high-reflection glaze layer with a composite structure is 18-30 μm.

12. The high reflective glaze layer according to any one of claims 1 to 3 and 6, It is characterized in that There are clear boundaries between the reflective layer and the surface layer, and between the reflective layer and the surface of the substrate glass.

13. A method for producing a high-reflective glaze layer with a composite structure according to any one of claims 1 to 12, It is characterized in that The production method comprises: Step (1): uniformly mixing the high-temperature binder phase and the first varnish to obtain a first slurry; Step (2): uniformly mixing the white filler and the second varnish to obtain a second slurry; Step (3): coating the second slurry and the first slurry on the substrate glass in sequence, and then tempering the substrate glass in a furnace to form a high-reflection glaze layer with a composite structure on the substrate glass.

14. The method according to claim 13, It is characterized in that The coating includes printing, roller coating or spraying.

15. The method according to claim 13 or 14, It is characterized in that The temperature of the furnace tempering is 690-740° C., and the time is 90-115 seconds.

16. A back plate glass, comprising a substrate glass and a glaze layer arranged on the surface thereof, It is characterized in that The glaze layer is a high-reflective glaze layer with a composite structure as described in any one of claims 1 to 12.

17. A photovoltaic module, It is characterized in that The photovoltaic module comprises the back panel glass according to claim 16.

18. The photovoltaic module according to claim 17, It is characterized in that The photovoltaic module is a double-glass photovoltaic solar module.

Citation Information

Patent Citations

  • Preparation and application of reflecting type fluorescent glass light conversion assembly

    CN105693108A

  • Reflecting coating of double-glass assembly and preparation method of reflecting coating

    CN113998901A

  • Environment-friendly high-reflection ink coating for photovoltaic glass and preparation method of environment-friendly high-reflection ink coating

    CN116239312A

  • Laminated glaze-plated layer suitable for photovoltaic module, preparation method of laminated glaze-plated layer, photovoltaic backboard semi-tempered glaze-plated glass and photovoltaic module

    CN117550808A

  • Preparation method of photovoltaic module

    CN117645814A

Cited By

  • Highly reflective glaze layer having composite structure and manufacturing method therefor, back sheet glass, and photovoltaic module

    WO2026040863A1